In Praise of Meliboeus: Calpurnius Siculus and Columella. (November 2021) - Nauta, Ruurd
Abstract: In discussion over the dating of the Bucolics of Calpurnius Siculus, an important role has always been played by attempts to identify the character of Meliboeus, who is to be read as a bucolic allegory of the poet's patron. By providing a new interpretation of the description of Meliboeus' literary production, I argue that he must be the agricultural writer Columella. A consideration of other aspects of Meliboeus confirms this identification, as does the analysis of a number of significant allusions to De cultu hortorum, the poem that makes up the tenth book of Columella's De re rustica . I then establish the date of Columella and discuss the consequences for dating Calpurnius, placing some parts of his book later in the reign of Nero than has been customary.